Development of a Science Instructional Model Based on Collaborative Problem Solving Framework for Students of the Faculty of Education, Chiang Mai Rajabhat University - Jutamas Noonchart (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this study was to develop science teaching by using collaborative problem solving concept and to compare the collaborative problem solving skills of students between before and after learning science by using and not using collaborative problem solving concepts. 60 students who studied elementary education major of Faculty of Education at Chiang Mai Rajabhat University, 2018 in class no.1 (30 students) and in class no.2 (30 students) were drawn to be the sample of the study. They were selected from purposive sampling. The results were found as follows: 1) science teaching model by using collaborative problem solving concept of Faculty of Education students at Chiang Mai Rajabhat University had 7 components that are testing of the 7 learning units: unit 1 (ecosystem), unit 2 (natural resources), unit 3 (genetic), unit 4 (substance and substance’s property), unit 5 (force and motion), unit 6 (energy) and unit 7 (eclipse). There were development with a performance from 198 to 468 with students in class no.1 (The experimental group that received collaborative problem solving concept teaching), but it was lower than the 500 that was a performance benchmark; 2) it was found that the development of science teaching by using collaborative problem solving model with the students of the Faculty of Education, Chiang Mai Rajabhat University between students using before class no.1 and after studying in class no.1, it was shown that the group of students using collaborative problem solving model class no.1 had higher academic results than before study and has a higher score than classroom 2, which did not use collaborative problem solving model with a statistical significance of 0.05.